Adsorptive-Photocatalytic Performance for Antibiotic and Personal Care Product Using Cu0.5Mn0.5Fe2O4 - Chanat Chokejaroenrat; Chainarong Sakulthaew; Athaphon Angkaew; Apiladda Pattanateeradetch; Wuttinun Raksajit; Kanokwan Teingtham; Piyaporn Phansak; Pawee Klongvessa; Daniel D. Snow; Clifford E. Harris; Steve D. Comfort (MDPI AG, 2023)
The amount of antibiotics and personal care products entering local sewage systems and ultimately natural waters is increasing and raising concerns about long-term human health effects. We developed an adsorptive photocatalyst, Cu0.5Mn0.5Fe2O4 nanoparticles, utilizing co-precipitation and calcination with melamine, and quantified its efficacy in removing paraben and oxytetracycline (OTC). During melamine calcination, Cu0.5Mn0.5Fe2O4 recrystallized, improving material crystallinity and purity for the adsorptive-photocatalytic reaction. Kinetic experiments showed that all four parabens and OTC were removed within 120 and 45 min. We found that contaminant adsorption and reaction with active radicals occurred almost simultaneously with the photocatalyst. OTC adsorption could be adequately described by the Brouers-Sotolongo kinetic and Freundlich isotherm models. OTC photocatalytic degradation started with a series of reactions at different carbon locations (i.e., decarboxamidation, deamination, dehydroxylation, demethylation, and tautomerization). Further toxicity testing showed that Zea mays L. and Vigna radiata L. shoot indexes were less affected by treated water than root indexes. The Zea mays L. endodermis thickness and area decreased considerably after exposure to the 25% (v/v)-treated water. Overall, Cu0.5Mn0.5Fe2O4 nanoparticles exhibit a remarkable adsorptive-photocatalytic performance for the degradation of tested antibiotics and personal care products.